Bilans ChZT w biologicznym oczyszczaniu ścieków osadem czynnym - cz. 1. skala laboratoryjna = COD balance in biological treatment of wastewater - part 1. laboratory scale - Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, the bases of COD balancing in aerobic, anoxic and anaerobic activated sludge systems were introduced. Literature data has been showing, that simulations of balances COD close 100% are possible for aerobic reactors or anoxic/aerobic systems. On systems including anaerobic zones the balance of COD is close maximally in 85%.
Keywords: bilans ChZT; węgiel organiczny; osad czynny; usuwanie azotu; balance of COD; organic carbon; activated sewage sludge; nitrogen removal